PEMBELAJARAN FIQIH BERBASIS KECAKAPAN ABAD 21 PADA SISWA KELAS V - Yassinta Yassinta (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2017)
The purpose of this study is to reveal about: 1) The steps for implementing 21st century skills-based fiqh learning for fifth grade students at Madrasah Ibtidaiyah Negeri 2 Sambas for the 2020-2021 academic year; 2) The results of the implementation of 21st century skills-based fiqh learning for fifth grade students at Madrasah Ibtidaiyah Negeri 2 Sambas for the 2020-2021 school year. The results showed that; The application of Fiqh learning in class V MIN 2 Sambas is quite good. This can be seen from the learning planning in class V using the 2013 curriculum (k-13) with 4 C skills (Critical and Problem solving skills/critical skills and problem solving, Collaboration skills/collaboration, Communication skills/communication, and Creativity and Innovation skills /creative and innovation). The learning process in class V learning fiqh in class is by implementing 3 learning materials used by fiqh teachers in teaching class V MIN 2 Sambas, namely qurban worship, procedures for the pilgrimage, and procedures for performing Umrah. In addition, the approach used is scientific with cooperative learning strategies, while the learning methods are modeling, question and answer, discussion, and assignments. There are 3 stages of fiqh learning, starting from the opening, core and closing activities. The results of the implementation of 21st century skills-based Fiqh learning in class V MIN 2 Sambas students in class V MIN 2 Sambas are quite good and include 3 aspects that are assessed, namely cognitive aspects (knowledge), affective aspects (attitudes), and psychomotor aspects (skills).